Evaluation of Postoperative Pain in Periodontal Flap Surgery with and without Photobiomodulation using Diode LASER: A Split-mouth Randomised Controlled Study - Neeraj Chandrahas Deshpande; Aayushi Shah; Monali Amit Shah (Journal of Clinical and Diagnostic Research)
Introduction: Flap surgery is used to treat deep periodontal pockets and recent innovations like Low-level LASER Therapy (LLLT), or Photobiomodulation (PBM), help reduce postsurgical pain. LLLT works by emitting red or infrared light at wavelengths between 660 and 940 nm, which penetrates tissues and interacts with cytochrome c oxidase to modulate immune responses, reduce inflammation and ease pain, promoting faster healing.